getphylo: rapid and automatic generation of multi-locus phylogenetic trees - T. J. Booth; S. Shaw; P. Cruz-Morales; T. Weber (BMC Bioinformatics)
Abstract Background The increasing amount of genomic data calls for tools that can create genome-scale phylogenies quickly and efficiently. Existing tools rely on large reference databases or require lengthy de novo calculations to identify orthologues, meaning that they have long run times and are limited in their taxonomic scope. To address this, we created getphylo, a python tool for the rapid generation of phylogenetic trees de novo from annotated sequences. Results We present getphylo (Genbank to Phylogeny), a tool that automatically builds phylogenetic trees from annotated genomes alone. Orthologues are identified heuristically by searching for singletons (single copy genes) across all input genomes and the phylogeny is inferred from a concatenated alignment of all coding sequences by maximum likelihood. We performed a thorough benchmarking of getphylo against two existing tools, autoMLST and GTDB-tk, to show that it can produce trees of comparable quality in a fraction of the time. We also demonstrate the flexibility of getphylo across four case studies including bacterial and eukaryotic genomes, and biosynthetic gene clusters. Conclusions getphylo is a quick and reliable tool for the automated generation of genome-scale phylogenetic trees. getphylo can produce phylogenies comparable to other software in a fraction of the time, without the need large local databases or intense computation. getphylo can rapidly identify orthologues from a wide variety of datasets regardless of taxonomic or genomic scope. The usability, speed, flexibility of getphylo makes it a valuable addition to the phylogenetics toolkit.